GAYA PENYUTRADARAAN HAYAO MIYAZAKI (Studi Kasus: Nausicaä of the Valley of the Wind, Spirited Away dan Princess Mononoke) - Caniah, Cici (Institut Seni Budaya Indonesia Bandung, 2017)
Animated films are growing rapidly in line with technology as well as sophisticated software support. Its use has encouraged animated filmmakers to be creative in both the story and the audio-visual quality. This paper raised the style of directing animated films from the style of Hayao Miyazaki. Hayao Miyazaki has its own concept and technique in concocting the works of the film. Until now, he has scored many awards. Traditional animation techniques are not as easy and as fast as the use of modern (digital) animation techniques. But he held fast and never dampened his passion to be able to create animations as well as animated films produced by Disney. He visualizes the scenario through his distinctive cinematic, for him the film is believed to have the freedom of creating images and hand drawings on paper is the fundamentals of animation. Technical data analysis is done based on auteur theory and qualitative approach to get an idea of the factors that influence Hayao Miyazaki in creating film work. The films analyzed in this paper are Nausicaä of the Valley of the Wind, Spirited Away and Princess Mononoke representing the work of Hayao Miyazaki. This study demonstrates the similarity of narrative created themes that address environmental issues, human relationships with nature and technology, and how difficult it is to safeguard the ethics of peace.